2019
DOI: 10.3390/en12224284
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution of Split-Injected Fuel Spray at Elevated Chamber Pressures

Abstract: For reducing soot and NOx emissions, an effective method is to apply split injection strategies. In this research, characteristics of split injection were investigated by applying the pilot-main injection strategy and main-post injection strategy. The injection mass of fuel with the two strategies was measured by an in-house fuel injection rate test system based on the Bosch method. The development of spray tip and tail penetrations, as well as the evolvement of the spray angle when applying these two injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In single injections, the start of combustion (SOC) can be identified by the high rate of heat release and the increase in chamber pressure present during the premixed combustion of the second stage, which, from the optical point of view is visualized as a sudden radial expansion [31]. This is valid for the first pulse in multiple injections, nonetheless, this pulse creates local conditions that could promote a faster SOC for the second injection [32] and the radial expansion would be very small [3] or non-existent, as is seen in Figure 5. Besides, once the thermal radiation from soot appeared in the frames, the intensity levels of these pixels resembled the background, creating problems in contour depiction.…”
Section: Novel Methods For Decoupling the Start Of Combustion Of The Second Pulsementioning
confidence: 99%
“…In single injections, the start of combustion (SOC) can be identified by the high rate of heat release and the increase in chamber pressure present during the premixed combustion of the second stage, which, from the optical point of view is visualized as a sudden radial expansion [31]. This is valid for the first pulse in multiple injections, nonetheless, this pulse creates local conditions that could promote a faster SOC for the second injection [32] and the radial expansion would be very small [3] or non-existent, as is seen in Figure 5. Besides, once the thermal radiation from soot appeared in the frames, the intensity levels of these pixels resembled the background, creating problems in contour depiction.…”
Section: Novel Methods For Decoupling the Start Of Combustion Of The Second Pulsementioning
confidence: 99%
“…According to Shundoh et al [172], it was found that combination of pre-injection and high-pressure injection in a high-speed engine leads to a significant reduction in NOx and smoke emissions by 35% and 60-80%, respectively. The main injection is split several times to improve the mixture formation process [173] and prevent the formation of BC. As shown in Figure 13, splitting the main injection or post injection can prevent the accumulation of excessively rich fuel and promote the accelerated oxidation of the high-concentration BC particles in the spray head.…”
Section: Injection Strategymentioning
confidence: 99%
“…Figure 11 shows the results of spray angle evolvements when applying injection strategy under the same injection pressure, and density of the fuel conditions had shown with only different cylinder combustion chamber geometry. The reason for the large spray angle in the initial injection phase because that the fuel was injected into a relatively stationary air environment and the air at the nozzle outlet was squeezed and pushed into the radial direction however, the spray angle remains nearly stable during the later injection stage ( Taşkiran and Ergeneman, 2011 ; Payri et al., 2017 ; Wu et al., 2019 ). This can be attributed to the increased momentum exchange at higher surrounding gas densities as the fuel droplets are more closely surrounded by environmental gases.…”
Section: Simulation Of Fuel Sprays In the Swirling Air Flowmentioning
confidence: 99%